A systematic review of the criterion validity and reliability of technical and tactical field-based tests in soccer - Clemente, F. M.; Praça, G.; Oliveira, R.; Aquino, R.; Araújo, R.; Silva, R.; Sarmento, H.; Afonso, J. (International Journal of Sports Science & Coaching, 2022)
Background Field-based tests are important since they can guarantee ecological validity. Although most such tests are designed to assess physical fitness, tactical and technical dimensions are also determinants in a full battery of tests.